Improving the world's financial architecture: The role of the IMF - Horst Siebert (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1999)
The IMF must change its sanction and incentive systems so that the next crisis is more likely to be prevented. It should concentrate more on ex ante prevention, which can be done by clearly specifying the rules that will be applied ex post. It should also rely more on automatic mechanisms that operate through the market in order to get to the roots of a potential crisis. Ex post, i.e., when a currency crisis has already occurred, the IMF can only play a limited role in mitigating the crisis. The IMF cannot play the same role for sovereign creditors as national institutions do in the case of illiquidity of domestic banks and firms. It cannot take over the role of a bankruptcy court judge. The IMF cannot credibly play the role of a lender of last resort. First, the lender of last resort lends to financial institutions, while the IMF lends to national governments when they run into trouble. Second, the national lender of last resort can print money and can thus credibly stop a crisis. For the IMF, this is not possible. Therefore, the central banks will have to play the role of a lender of last resort in a coordinated action if a systemic crisis for the world economy develops. The IMF is involved only initially, somewhat easing the task of the true lender of last resort, the central banks. Ex post, the crisis has to be mitigated in such a way that dealing with the crisis does not generate processes and behavior that give rise to the next currency crisis. The IMF should avoid setting wrong incentives. -The IMF should not make up for national political mistakes and national institutional deficiencies. -The IMF should change its policy and not implicitly defend a pegged exchange rate. -The IMF should stop lending to countries that are in arrears to private creditors and bondholders (sovereign arrears) and should return to its previous policy. -The IMF should rule out credits to sovereign debtors if the government of a country takes over guarantees for nonperforming private loans, thus socializing private default risks. -The IMF should think about scaling down its level of operations. This recommendation is in stark contrast to the somewhat expansionist doctrine now being propagated by the IMF. Ex ante, some new rules should be established. In analogy to the "polluter-pays principle" of environmental economics, a "troublemaker-pays principle" should be used. This would hopefully internalize the social costs caused by countries behaving in a manner that generates instability and adds to the risk of a systemic crisis. - The IMF should improve its early warning system, create more transparency, and provide more information, including high-frequency debt-monitoring systems. The international community should intensify discussions on standards that countries would have to follow. -The IMF should specify the sanctions to be levied when standards are not respected. A penalty rate should be charged if additional credit is provided. Requiring collateral would also be a strong incentive to sovereign borrowers to build up assets. - The IMF should define the policy it would pursue in the case of a crisis more credibly. It should move away from the discretionary decisions of its case-by-case approach (favored by US pragmatism) and bind itself by rules (favored by the Europeans). One way to improve credibility of IMF policy would be to rely more on automatic mechanisms that internalize the external effects of national instability behavior. Thus, the IMF should not be a silent supervisor who deliberates behind closed doors. It is better to blow the whistle and apply the brakes before the train crashes. Involving the private sector in the case of a crisis is an important means of internalizing the social costs of instability. In contrast to the mostly used American-style bonds, British-style trustee deed bonds are more appropriate to manage crises as they include sharing clauses and majority rules.
Keywords: 330; Internationales Währungssystem; Internationale Wirtschaftsorganisation; Reform; Internationaler Kredit; Moral Hazard; Internalisierung externer Effekte; Welt